An ~130 kyr Record of Surface Water Temperature and δ18O From the Northern Bay of Bengal: Investigating the Linkage Between Heinrich Events and Weak Monsoon Intervals in Asia. Issue 2 (18th February 2020) - Lauterbach, Stefan; Andersen, Nils; Wang, Yiming V.; Blanz, Thomas; Larsen, Thomas; Schneider, Ralph R.
Abstract: Millennial‐scale reductions in monsoon precipitation, so‐called Weak Monsoon Intervals (WMIs), have been identified in numerous paleoclimate records across the Afro‐Asian monsoon domain throughout the last glacial‐interglacial cycle. These are considered the regional response to cooling during Heinrich events in the North Atlantic realm and several mechanisms have been suggested to explain this hemisphere‐scale climatic teleconnection. In particular, reductions in Indian Ocean sea surface temperature (SST) have been proposed as the linking element between Heinrich events and WMIs. However, the validity of this relationship has only been demonstrated for the last ~20 kyr, leaving unresolved whether it also holds on longer time scales. Here we present a new paired record of planktonic foraminifera‐based δ 18 Osw‐ivc and U K' 37 ‐based SST from the northern Bay of Bengal, covering the last ~130 kyr. The δ 18 Osw‐ivc record clearly reflects orbitally paced changes of Indian Summer Monsoon intensity superimposed by centennial‐ to millennial‐scale WMIs that occurred synchronously to North Atlantic Heinrich events. Comparison with the U K' 37 ‐based SST reconstruction reveals, however, that WMIs in most cases were not paralleled by ocean surface cooling, questioning whether Indian Ocean SST lowering was the linking element between Heinrich events and reductions in monsoon precipitation in Asia also during the last glacial period. Key Points: A paired record of planktonic foraminifera δ 18 O and U K' 37 ‐based sea surface temperature (SST) from the northern Bay of Bengal is provided Short‐term reductions in Indian Summer Monsoon (ISM) precipitation occurred parallel to North Atlantic Heinrich events Reductions in ISM precipitation during the last ~130 kyr were apparently not always connected to changes in Bay of Bengal SST